Seroprevalence of hepatitis E among hospitalized patients in Slovakia: first report - Paraličová, Zuzana; Halánová, Monika; Schréter, Ivan; Kalinová, Zuzana; Novotný, Martin; Sekula, Jakub; Paralič, Ján; Kristián, Pavol (Central European Journal of Public Health, 2020)
OBJECTIVE: Hepatitis E infection is one of the most frequent acute hepatitis in the world. Currently five human genotypes with different geographical distributions and distinct epidemiologic patterns are identified. In Slovakia, only rare cases of hepatitis E have been reported in recent years. Therefore, the aim of the study was to evaluate the prevalence of anti-HEV total antibodies and the main risk factors for HEV in the general population in Eastern Slovakia. METHODS: Detection of anti-HEV total antibodies samples was done by a commercial enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Of 175 hospitalized patients included in the study, 76 (43.5%) showed positivity for anti-HEV total antibodies. No statistically significant differences were found in anti-HEV positivity between men and women or in the groups of different living areas (town/village - urban/rural). CONCLUSION: Prevalence of anti-HEV total antibodies of hospitalised patients was high. The risk factor significantly associated with antibody positivity was eating raw meat. Other factors, such as sex, age, living area and contact with animals were not associated with antibody positivity.
Keywords: Humans; Slovakia; hepatitida - protilátky; hepatitida E; Slovenská republika; virus hepatitidy E; ELISA; mužské pohlaví; Risk Factors; Enzyme-Linked Immunosorbent Assay; séroepidemiologické studie; Hepatitis Antibodies; rizikové faktory; hospitalizace; Hospitalization; Hepatitis E virus; ženské pohlaví; Female; Seroepidemiologic Studies; lidé; Male; Hepatitis E